A Study on English Listening Activity of “Shadowing” in Indonesian Students - Tribekti Maryanto Agustinus; Nur Rini; Mitchell Clark (Soshum: Jurnal Sosial dan Humaniora, 2019)
Obviously listening improves speaking skills. Polytechnic graduates are to have business transaction skills. Meanwhile, the time allotment for English class sessions is limited. Therefore, the teachers are to promote students’ autonomous learning through listening. This study investigates how the students major in commerce at an Indonesian polytechnic complete listening tasks and attitudes toward the acquisition of listening skills. Training on how to complete the listening activities through shadowing was carried out with 43 students. A questionnaire was distributed to find out the students’ views on the suggested listening activities and their opinions to improve them. The study found students’ preferences in practicing listening; most employed 1 or 2 or 3 steps. Most include initial listening, reading, and one of the types of shadowing - silent shadowing with reading or synchronized shadowing or prosody shadowing. None of the students was interested in doing silent shadowing. They admitted that their listening most improved their pronunciation and enriched vocabulary. They expected more lecturer engagement in controlling their listening activity. By better understanding the students’ needs and opinions, strategies to encourage autonomous learning can be improved